A review of characteristics and experiences of decentralization of education - Mwinjuma, Juma Saidi; Abd Kadir, Suhaida; Hamzah, Azimi; Basri, Ramli (Australian International Academic Centre, 2015)
This paper scrutinizes decentralization of education with reference to some countries around the world. We consider discussion on decentralization to be complex, critical and broad question in the contemporary education planning, administration and politics of education reforms. Even though the debate on and implementation of decentralization education can result from differences in ideological and philosophical backgrounds (McGinn & Welsh, 1999), in this scrutiny we begin by theorizing the concept, provides dimensions and goals of decentralization and demonstrate how decentralization has been implemented in some countries. Finally, conclusion is assumed in this debate as a summary and a conduit to further discussion and investigation of educational decentralization.